2009
DOI: 10.3945/ajcn.2008.27097
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of micronutrient status in adolescent pregnancy

Abstract: Background: Adolescents are more likely than adults to consume energy-dense, micronutrient-poor diets and to experience adverse pregnancy outcomes. Objectives: The objectives were to assess micronutrient intake and blood biomarkers prospectively in pregnant adolescents recruited to the About Teenage Eating (ATE) Study and to determine associations with pregnancy outcome. Design: Pregnant adolescents (n ¼ 500) were recruited from 2 UK inner city populations. Dietary intake was assessed with three 24-h dietary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(162 citation statements)
references
References 47 publications
7
148
1
6
Order By: Relevance
“…The prevalence of iron deficiency in pregnant women in the studies conducted in UK [32]; in China [33]; and in India [16] was 34, 42.6 and 73.4 % respectively. The high prevalent of iron deficiency amongst pregnant women found in the present study was possibly due to the inadequate iron consumption or the bread eaten by Iranian is made from flour of high extraction and without added leaven.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of iron deficiency in pregnant women in the studies conducted in UK [32]; in China [33]; and in India [16] was 34, 42.6 and 73.4 % respectively. The high prevalent of iron deficiency amongst pregnant women found in the present study was possibly due to the inadequate iron consumption or the bread eaten by Iranian is made from flour of high extraction and without added leaven.…”
Section: Discussionmentioning
confidence: 99%
“…Mean folate intake in European populations ranges from 180 to 280 μg/day [5,29,139], which is not sufficient to prevent folate-responsive NTD cases. In addition, factors like smoking, very young age, and lack of knowledge about the importance of folate supplementation before pregnancy can adversely affect the folate status and increase the risk of having a child with a NTD.…”
Section: Strategies To Prevent Ntds By Improving Maternal Folate Statusmentioning
confidence: 99%
“…Recently, one study has shown that most women do not improve their dietary and lifestyle patterns in pregnancy (3). Decreased nutrient delivery to the fetus also occurs in teenage pregnancy (4) and during pregnancy in women over 35 y of age (5). Severe global reduction in nutrition during pregnancy has long been known to result in fetal growth restriction and to cause permanent brain dysfunction, especially cognitive and behavior deficits (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%